Prostate cancer mortality risk in relation to working underground in the Wismut cohort study of German uranium miners, 1970–2003 - Walsh, Linda (BMJ Group, 2012)
OBJECTIVE: A recent study and comprehensive literature review has indicated that mining could be protective against prostate cancer. This indication has been explored further here by analysing prostate cancer mortality in the German ‘Wismut’ uranium miner cohort, which has detailed information on the number of days worked underground. DESIGN: An historical cohort study of 58 987 male mine workers with retrospective follow-up before 1999 and prospective follow-up since 1999. SETTING AND PARTICIPANTS: Uranium mine workers employed during the period 1970–1990 in the regions of Saxony and Thuringia, Germany, contributing 1.42 million person-years of follow-up ending in 2003. OUTCOME MEASURE: Simple standardised mortality ratio (SMR) analyses were applied to assess differences between the national and cohort prostate cancer mortality rates and complemented by refined analyses done entirely within the cohort. The internal comparisons applied Poisson regression excess relative prostate cancer mortality risk model with background stratification by age and calendar year and a whole range of possible explanatory covariables that included days worked underground and years worked at high physical activity with γ radiation treated as a confounder. RESULTS: The analysis is based on miner data for 263 prostate cancer deaths. The overall SMR was 0.85 (95% CI 0.75 to 0.95). A linear excess relative risk model with the number of years worked at high physical activity and the number of days worked underground as explanatory covariables provided a statistically significant fit when compared with the background model (p=0.039). Results (with 95% CIs) for the excess relative risk per day worked underground indicated a statistically significant (p=0.0096) small protective effect of −5.59 (−9.81 to −1.36) ×10(−5). CONCLUSION: Evidence is provided from the German Wismut cohort in support of a protective effect from working underground on prostate cancer mortality risk.